STIM1-mediated bidirectional regulation of Ca2+ entry through voltage-gated calcium channels (VGCC) and calcium-release activated channels (CRAC) - Harraz, Osama F.; Altier, Christophe (Frontiers in Cellular Neuroscience, 2014)
The spatial and temporal regulation of cellular calcium signals is modulated via two main Ca2+ entry routes. Voltage-gated Ca2+ channels (VGCC) and Ca2+-release activated channels (CRAC) enable Ca2+ flow into electrically excitable and non-excitable cells, respectively. VGCC are well characterized transducers of electrical activity that allow Ca2+ signaling into the cell in response to action potentials or subthreshold depolarizing stimuli. The identification of STIM and Orai proteins has provided significant insights into the understanding of CRAC function and regulation. This review will summarize the current state of knowledge of STIM-Orai interaction and their contribution to cellular Ca2+ handling mechanisms. We will then discuss the bidirectional actions of STIM1 on VGCC and CRAC. In contrast to the stimulatory role of STIM1 on Orai channel activity that facilitates Ca2+ entry, recent reports indicated the ability of STIM1 to suppress VGCC activity. This new concept changes our traditional understanding of Ca2+ handling mechanisms and highlights the existence of dynamically regulated signaling complexes of surface expressed ion channels and intracellular store membrane-embedded Ca2+ sensors. Overall, STIM1 is emerging as a new class of regulatory proteins that fine-tunes Ca2+ entry in response to endoplasmic/sarcoplasmic reticulum stress.